Desvendando os efeitos não autônomos de Dicer no controle da proteostase celular em caenorhabditis elegans e camundongos - Pinca, Ana Paula Forti [UNIFESP] (2017)
Age-related proteotoxicity is the major cause of neurodegenerative diseases like Alzheimer’s and Huntington’s. Small RNAs appear to be excellent candidates in controlling cellular proteostasis since they selectively inhibit protein synthesis, are expressed in temporal or tissue-specific manners, are regulated by interventions that affect lifespan, and act in cell autonomous and non-autonomous manners in multicellular organisms. Our aim in this study was to test if Dicer, which becomes rate-limiting in miRNA biogenesis with aging, is able to control the susceptibility to age-related proteotoxic stress as measured by paralysis and lifespan analyses in C. elegans, and by behavior and biochemical analyses in mice. First, we silenced Dicer in all tissues but the neurons in wild type N2 worms. Surprisingly, Dicer RNAi in adult N2 worms delayed age-related paralysis, and this was reversed when proteotoxicity was induced in muscle with overexpression of polyglutamine (polyQ) peptides. Muscle-, neuron- or intestine-specific Dicer RNAi did not affect the proteostasis in wild type or polyQ worms. Our data suggests a scenario where silencing of Dicer in all tissues except in the tissue where age-related proteotoxicity is more relevant confers beneficial effects. Consistent with a cell non-autonomous effect, some of our previouslyresults showed that intestine-specific Dicer overexpression accelerates age-related paralysis in muscle-selective polyQ worms. Thus, we may suggest there is a balance of Dicer levels among tissues that determines age-related proteostasis decline, in which higher levels in neurons vs. other tissues is beneficial. However, the effects of Dicer appear to be protein specific, since the same thing did not occur in worms that aggregate beta-amyloid proteins rather than polyglutamines. In addition, we have seen a small beneficial effect of Dicer knockout in the adipose tissue of transgenic male mice model for Alzheimer's disease, suggesting that Dicer possibly exerts some non-autonomous effect on cellular proteasase in mammals as well.